Measuring circularity from buildings to neighbourhoods - Vanessa Gomes; Sara Valdivia; Lizzie Pulgrossi; Maristela Gomes da Silva (Acta Polytechnica CTU Proceedings, 2022)
The circular economy (CE) aims to eliminate the concept of pollution and waste generation, maintain the integrity of the product over several use cycles, and focus on closing material and energy loops. Circularity metrics are relevant for monitoring, reporting and communicating CE implementation progress. Applied to buildings, these metrics deliver structured assessments through standardized indicators, which establish a common language among the agents involved, help implement strategies to assess the circular potential of technical options. Studies dealing with circularity metrics for buildings are still scarce and somewhat variable within an overall common framework. Applications to neighbourhoods are even more incipient. This study applied selected metrics to two building cases with different constructive characteristics, to improve the understanding on how information on circularity is conveyed. The selected metrics highlighted the circularity challenges for the two building designs. However, such metrics disregard the environmental impacts required to induce circular flows and loop closure. It is herein proposed that such metrics are paired with environmental performance profiles produced by e.g., life cycle assessments (LCA). The concept of "nested indicators" could be applied to neighbourhood and city scales by referring to the LCA concept of functional equivalency as the "relevance"  weighting criterion.